Energy recovery in oil refineries through the installation of axial Pumps-as-Turbines (PaTs) in a wastewater sewer: a case study. (February 2019) - Renzi, Massimiliano; Rudolf, Pavel; Štefan, David; Nigro, Alessandra; Rossi, Mosè
Abstract: This paper analyses an energy recovery solution for the application in an oil refinery, which has undergone significant changes in the last decades due to the construction of different plants, services, storage and logistics systems. Nowadays, with the aim to reduce the water contamination close to the refinery, the local regulations imposed to introduce solutions for the treatment of the groundwater underneath the oil treatment plants. In order to reclaim the site and to safeguard the areas close to the oil refinery, an intervention named "Pump & Treat" was adopted by an Italian company which consists in pumping up the underground water and treating it to remove any trace of polluting agent. Subsequently, a part of the treated water is discharged, by gravity, into the sea through a wastewater sewer. An Axial-Flow Pump (AFP) is studied in both pump and turbine modes for being installed in the wastewater sewer of the analysed oil refinery. After evaluating the availability of flow rate and head, the design characteristics of a proper axial turbine were identified. Computational Fluid Dynamics (CFD) simulations of an AFP are performed in both pump and turbine modes. The obtained results were used for scaling down the hydraulic machine and for defining a new one, properly adapted for the wastewater sewer, as energy recovery unit. The selected axial Pump-as-Turbine (PaT) allowed to achieve an economic saving of about 1706 €/year, leading to a Pay-Back Period (PBP) of about 1 year and 10 months.